Multifocal infantile hemangiomas associated with concomitant giant hepatic rapidly involuting congenital hemangioma. Issue 5 (9th July 2020) - Wessman, Laurel L.; Mori, Westley S.; Totoraitis, Kristin; Murati, Michael; Maguiness, Sheilagh
Abstract: We present a 9‐day‐old girl with multifocal cutaneous and hepatic infantile hemangiomas as well as a hepatic rapidly involuting congenital hemangioma. These two distinct vascular tumors have rarely been reported to co‐occur. We additionally review the sonographic features that distinguish a hepatic congenital hemangioma from the hepatic infantile hemangioma.